Mapping of the sGC Stimulator BAY 41-2272 Binding Site on H-NOX Domain and Its Regulation by the Redox State of the Heme - Makrynitsa, Garyfallia I.; Argyriou, Aikaterini I.; Zompra, Aikaterini A.; Salagiannis, Konstantinos; Vazoura, Vassiliki; Papapetropoulos, Andreas; Topouzis, Stavros; Spyroulias, Georgios A. (Frontiers in Cell and Developmental Biology, 2022)
Soluble guanylate cyclase (sGC) is the main receptor of nitric oxide (NO) and by converting GTP to cGMP regulates numerous biological processes. The β1 subunit of the most abundant, α1β1 heterodimer, harbors an N-terminal domain called H-NOX, responsible for heme and NO binding and thus sGC activation. Dysfunction of the NO/sGC/cGMP axis is causally associated with pathological states such as heart failure and pulmonary hypertension. Enhancement of sGC enzymatic function can be effected by a class of drugs called sGC “stimulators”, which stimulate the reduced ferrous-bound, native form of sGC (Fe(II)sGC) NO-independently and synergize with low NO concentrations. Until recently, our knowledge about the binding mode of stimulators relied on low resolution cryo-EM structures of human sGC in complex with known stimulators, while information about the mode of synergy with NO is still limited. Herein, we couple NMR spectroscopy using the H-NOX domain of the Nostoc sp. cyanobacterium with cGMP determinations in aortic smooth muscle cells (A7r5) to study the impact of the redox state of the heme on the binding of the sGC stimulator BAY 41-2272 to the Ns H-NOX domain and on the catalytic function of the sGC. BAY 41-2272 binds on the surface of H-NOX with low affinity and this binding is enhanced by low NO concentrations. Subsequent titration of the heme oxidant ODQ, fails to modify the conformation of H-NOX or elicit loss of the heme, despite its oxidation. Treatment of A7r5 cells with ODQ following the addition of BAY 41-2272 and an NO donor can still inhibit cGMP synthesis. Overall, we describe an analysis in real time of the interaction of the sGC stimulator, BAY 41-2272, with the Ns H-NOX, map the amino acids that mediate this interaction and provide evidence to explain the characteristic synergy of BAY 41-2272 with NO. We also propose that ODQ can still oxidize the heme in the H-NOX/NO complex and inhibit sGC activity, even though the heme remains associated with H-NOX. These data provide a more-in-depth understanding of the molecular mode of action of sGC stimulators and can lead to an optimized design and development of novel sGC agonists.